2019
DOI: 10.1186/s12910-019-0347-0
|View full text |Cite
|
Sign up to set email alerts
|

How to effectively obtain informed consent in trauma patients: a systematic review

Abstract: BackgroundObtaining adequate informed consent from trauma patients is challenging and time-consuming. Healthcare providers must communicate complicated medical information to enable patients to make informed decisions. This study aimed to explore the challenges of obtaining valid consent and methods of improving the quality of the informed consent process for surgical procedures in trauma patients.MethodsWe conducted a systematic review of relevant English-language full-text original articles retrieved from Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 85 publications
1
50
0
4
Order By: Relevance
“… 5 , 6 However, STSMs are not without ethical issues; one of them is obtaining informed consent, 7 a process that nurtures 2 fundamental moral values: patient well-being and patient autonomy. 8 …”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 However, STSMs are not without ethical issues; one of them is obtaining informed consent, 7 a process that nurtures 2 fundamental moral values: patient well-being and patient autonomy. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Patients who received video information were more satis ed than patients who received written or verbal information. [40] The present results show that the video-assisted informed consent intervention resulted in improved understanding compared with the conventional informed consent discussion.…”
Section: Discussionmentioning
confidence: 50%
“…Several strategies have been proposed to improve the consent process in the emergency setting. [40,15] One study reported that using information aids may improve parental satisfaction with surgical informed consent in children. [41] Another study revealed that visual aids may improve communication about surgery between pediatric surgeons and surrogates.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this reason in the hospital practice of our region, most often patients are giving inadequate information about their surgery before operation. 1,5,6,7,8 Seeking informed consent is often a formal act in which a patient's signature is obtained, with physicians believing that an important obligation has been fulfilled regardless of whether the patient has been provided with adequate information about the medical intervention that is about to take place. 1 Although this general observation, there is limited research is available from our country about the usual practice of preoperative informed consent.…”
Section: Introductionmentioning
confidence: 99%